An efficient approach for detecting atrial fibrillation in ischemic stroke patients using a wearable device: a prospective multicenter substudy of the STABLED trial - Saito, Tomonari; Nishiyama, Yasuhiro; Otsuka, Toshiaki; Sakamoto, Yuki; Okubo, Seiji; Iguchi, Yasuyuki; Yamaguchi, Keiji; Okada, Yasushi; Hamaguchi, Hirotoshi; Yonehara, Toshiro; Fukuzawa, Masayuki; Takita, Atsushi; et al. (Frontiers in Neurology, 2025)
ObjectiveStroke caused by atrial fibrillation (AF) is associated with high mortality and severe morbidity. Screening patients for AF may facilitate early initiation of anticoagulant therapy and prevent recurrent stroke; therefore, strategies to effectively detect AF in stroke patients are important.MethodsThis prospective multicenter study was conducted between April 27, 2020 and March 31, 2021 at seven sites in Japan, as a substudy of the STABLED trial, a multicenter prospective randomized study to evaluate the efficacy and safety of catheter ablation with anticoagulant therapy using edoxaban in patients with ischemic stroke and AF. This substudy included 241 patients who suffered ischemic stroke but had no diagnosis of AF. Patients were monitored with Duranta, a wearable non-invasive wireless patch ECG system. The primary outcome was the detection rate for AF while wearing Duranta.ResultsOf the 241 patients, 66.8% were men, and the mean age was 71.0 years. AF was detected in 21 of the 241 patients (8.7, 95% CI: 5.4–12.4) during follow-up using the Duranta wearable ECG system. ECG data were recorded for 7 days in all patients. The median number of days from stroke onset to Duranta placement was 2.0, but this duration varied considerably (median; IQR, 0–22.0). An adverse event of dermal pruritus was observed in 1 of the 241 patients (0.4%). Determinants for the detection of AF in patients with no previous history of AF were dyslipidemia and left atrial dimension.ConclusionWearable wireless patch ECG systems such as Duranta are simple and efficient devices for detecting AF. In patients with ischemic stroke and no diagnosis of AF, their use for detecting new AF may provide benefit through early initiation of anticoagulants and prevention of recurrent stroke.